Simultaneous Episodes of Heavy Rainfall in Morocco and Southern Alps: 1. Mesoscale Simulations and Episode Climatology (1979–2016). Issue 4 (12th February 2020) - Gangoiti, G.; Sáez de Cámara, E.; Alonso, L.; Iza, J.; García, J. A.; Valdenebro, V.; Gómez, M. C.; Navazo, M.; García, E.
Abstract: The torrential rain and southerly föhn episode on 14–16 November 2002 in the Alpine southside, which affected the Piedmont region, was concurrent with heavy rains in the northwest flanks of the Middle and High Atlas in Morocco. Both simultaneous rainfalls are analyzed, as well as the recent climatology of similar episodes. A mesoscale modelling system is used first to simulate the relevant atmospheric processes and then to map the evaporative sources of both targets. Moderate Resolution Imaging Spectroradiometer water vapor products, National Centers for Environmental Prediction reanalysis data sets, radiosondes, wind profilers, and surface rain gauges are used to substantiate the simulations. The evaporative source estimation is discussed in a companion article. The simultaneous episodes originated after the development of a narrow meridionally elongated upper level trough extending southward from the British Islands into Iberia, associated with a semi‐stationary large amplitude wave. A total of 43 similar episodes have been identified during the 38‐year period 1979–2016, averaging one episode per year. However, there is a large interannual variability, with several years with no episodes and, others, which can accumulate up to four episodes. The episode length shows also a high variability, from 2 to 7–8 days. The longest episodes usually include an enlarged "Mediterranean phase" for the rainfalls in the Alps. With respect to their seasonal variability, the largest fraction concentrates in autumn (60%), and no episodes are found from June to August. November accumulates the highest case occurrence (37%) and the observed variability cannot be explained by changes in the phase of the North Atlantic Oscillation. Key Points: A type of heavy rainfall episodes in southern Alps is concurrent with similar extraordinary events in the Middle and High Atlas in Morocco The episodes share a similar synoptic forcing, rainfall amount exceptionality and duration in both regions, S‐Alps and W‐Morocco During the last 38 years, similar episodes have occurred once a year with a large interannual variability and an autumn seasonal preference